The face validity and clinical utility of the Activity Card Sort – United Kingdom (ACS-UK). (August 2016) - Laver-Fawcett, Alison; Brain, Leanne; Brodie, Courtney; Cardy, Lauren; Manaton, Lisa
Introduction: The Activity Card Sort – United Kingdom version is a self-report interview assessment requiring older adults to sort activity photograph cards to evaluate their levels of participation. The face validity and clinical utility of the activity card sort – United Kingdom were explored. Method: The sample comprised 27 community dwelling older adults (>65 years) and eight assessors. The Activity Card Sort – United Kingdom was administered, followed by a semi-structured interview to explore participants' opinions and experiences of undertaking the assessment. Time taken to administer and score was measured. Results: Mean administration and scoring time was 14 minutes and 30 seconds, which was considered reasonable by older people and assessors. The majority of participants found the Activity Card Sort – United Kingdom straightforward, easy to do and considered activities and activity labels clear. All participants considered that photographs looked like the activities they were depicting. Participants made recommendations which have led to some improvements to the assessment. Conclusion: The Activity Card Sort – United Kingdom has good clinical utility in terms of ease of use and time required for administering and scoring the assessment. Face validity, in terms of acceptability, was good, but more detailed instructions in the manual will be required to guide therapists on how to explain the purpose of the assessment to clients.